The Early Modern Rationalists and Substantial Form - Viljanen, Valtteri (Zeta Books, 2025)
This paper argues that, contrary to what one might think, early modern rationalism displays an increasing and well-grounded sensitivity to certain metaphysical questions substantial form was designed to answer— despite the fact that the notion itself was in such disrepute, and emphatically banished from natural philosophy. This main thesis is established by examining the thought of Descartes, Spinoza, and Leibniz through the framework constituted by what have been designated as the two aspects, metaphysical and physical, of substantial form. This examination shows that Descartes ends up assigning to soul a notable metaphysical task formerly assigned to substantial form, whereas Spinoza advances a theory of essences motivated by the philosophical concerns behind the two aspects of substantial form. Leibniz finally makes a sharp distinction between natural philosophy and metaphysics as he develops a dynamistic theory that deliberately aims at understanding substantial form in a new fashion. This line of development is designated as one major factor contributing to the separation of philosophy and natural science.